The effects on sales when franchising a hotel - Curalli, Vito (Henry Stewart Talks, 2009)
Brand benefits for the franchisee, Brand benefits for the customer, Brand benefits for the sales department, National sales, National marketing, Local marketing, Partnerships, Technology tools for sales, Media, Multiple brands, Why franchise?